A novel linear ultrasonic motor with characteristic of variable mode excitation. (August 2017) - Zhou, Xiangyu; Zhang, Yi; Zhang, Qiang
Abstract: This article presents a novel linear ultrasonic motor with two operation modes. The stator of the motor can be divided as two transducers and two isosceles triangular beams. The first bending vibration modes and first longitudinal vibration modes of the stator are superposed as two operation modes respectively, and the variable mode control is realized by a special excitation method. The operating principle of the motor and the formation of the elliptical trajectory of the driving foot are analyzed, and the variable mode excitation method is illustrated. A prototype was made and experiment investigation of the motor characteristics at different operation mode, frequency and voltage are presented and compared. Testing results of the prototype shows that this motor can gain maximum speed of 114.6 mm/s and maximum thrust force 3.33 N under bending operation mode with exciting voltage of 400 VP-P, and it can gain maximum speed of 52 mm/s and maximum thrust force 2.35 N under longitudinal operation mode with exciting voltage of 400 VP-P . The major feature of the motor is that the variable mode control can be realized by using the method of variable mode excitation and switching the operation mode to broaden the working frequency bandwidth.